Hechos y Glosas - Junco, Alfonso; Amigo Jasén, Gustavo; Romero Pérez, Jesús (ECA: Estudios Centroamericanos, 1967)
No hay resúmenes disponibles. ECA Estudios Centroamericanos, Vol. 22, No. 223, 1967: 357-364.